DOP015 Dysregulation of cell-type-specific long ncRNA in the ileum of treatment naïve early onset Crohn disease. (16th January 2018) - Haberman, Y; BenShoshan, M; Di Segni, A; Dexheimer, P J; Braun, T; Weiss, B; Avivi, C; Barshack, I; Anikster, Y; Aronow, B; Hyams, J S; Kugathasan, S; et al.
Abstract: Background: Long non-coding RNAs (lncRNA) are key regulators of gene transcription and many show tissue-specific expression. We previously defined a novel inflammatory and metabolic ileal gene signature in treatment naïve paediatric Crohn disease (CD). We now extend our analyses to include potential regulatory lncRNA. Methods: Using RNAseq of the Crohn's & Colitis Foundation (CCF)-sponsored RISK study, we systematically profiled lncRNAs and protein-coding genes expression in 177 ileal biopsies. Co-expression analysis was used to identify functions and tissue-specific expression. RNA in situ hybridisation was used to validate expression. RT-PCR was used to test lncRNAs regulation by IL-1β in Caco-2 enterocytes. Results: We characterise widespread dysregulation of 459 lncRNA in the ileum of CD patients. Using only the lncRNA in discovery and independent validation cohorts showed as accurate patients' classification as the protein-coding genes, linking lncRNA to CD pathogenesis. Co-expression and functional annotation enrichment analyses across several tissues and cell types showed that the up-regulated LINC01272 is associated with a myeloid pro-inflammatory signature, while the down-regulated HNF4A-AS1 exhibits association with an epithelial metabolic signature. We confirmed tissue-specific expression in biopsies using in situ hybridisation, and validated regulation of prioritised lncRNA upon IL-1β exposure in differentiated Caco-2 cells. Finally, we identified significant correlations between LINC01272 and HNF4A-AS1 expression and more severe mucosal injury. Conclusions: We systematically define differentially expressed lncRNA in the ileum of newly diagnosed paediatric CD. We show lncRNA utility to correctly classify disease or healthy states and demonstrate their regulation in response to an inflammatory signal. These lncRNA, after mechanistic exploration, may serve as potential new tissue-specific targets for RNA-based interventions.